CYP2D6*4 polymorphism, tramadol treatment and its clinical impact in patients with postherpetic neuralgia. (June 2012) - Nasare, Namita Vilas; Deshmukh, Pravin Suryakantrao; Banerjee, Basu Dev; Mediratta, Pramod Kumari; Ahmed, Rafat S; Saxena, Ashok Kumar; Bhattacharya, Sambit Nath
Aim: The aim of this study was to investigate the associations between the CYP2D6*4 polymorphism, interindividual differences in CYP2D6 activity and adverse drug effects in postherpetic neuralgia (PHN) patients receiving tramadol.Patients & methods: The study comprised 158 patients (including 78 nonresponders and 80 responders) with PHN who were undergoing analgesic treatment at the Pain Clinic in the Out Patient Department of the University College of Medical Sciences, Guru Teg Bahadur Hospital (New Delhi, India). The numerical rating scale scores were measured at the resting and movement stages; Neuropathic Pain Symptom Inventory scores were evaluated by the treating physician. WHO-brief questionnaire scores for quality of life and adverse drug effects during the time of study were recorded. All samples were analyzed for the CYP2D6*4 polymorphism using the PCR-restriction fragmentation length polymorphism method.Results: The genotype distribution did not vary significantly among different age groups in nonresponders and responders. The CYP2D6*4 polymorphism was significantly associated with lower Neuropathic Pain Symptom Inventory (burning, squeezing stabbing and pressure) scores. The quality-of-life (sociological, psychological and environmental domains) scores correlated with CYP2D6*4 and showed significant results (p < 0.05) using a generalized linear model. No association was found between the physiological domain compared with the CYP2D6*4 allele (p > 0.05). In addition, the homozygous mutated CYP2D6*4 allele was not related to adverse effects of analgesic therapy.Conclusion: The CYP2D6*4 polymorphism may not be a predictor for treatment outcome of patients with PHN receiving tramadol. However, further investigation is required to confirm these findings in a larger sample size.